Pengaruh Kepemimpinan dan Motivasi terhadap Kinerja Karyawan Administrasi (Studi Kasus di PT Ketapang Subur Lestari, Field Karusen) - . Sugiyatno (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
The purpose of this research is to determine the influence of leadership and motivation on the performance of administrative employees at PT Ketapang Subur Lestari, Field Karusen. The data analysis technique used is multiple linear regression and uses the SPSS version 15 for windows software program. The result of data analysis show that the regression equation obtained is Y = 16.535 - 1.455X1 + 3.566X2. Hypothesis test result show that leadership has a negative and significant effect on employee performance, while motivation has a positive and significant effect on employee performance. The simultaneous test result show that all independent variables have a significant effect on employee performance. The influence of the independent variables (leadership and motivation) on the dependent variable (employee performance) is 71.9%; and 28.1% influenced by other variables outside the variables studied.